Determinants of Cognitive Impairment among The Elderly in Indonesia - Rismawaty Rismawaty; Sri Moertiningsih Adioetomo (Jurnal Berkala Kesehatan, 2021)
Impaired cognitive function is one of the health problems suffered by elderly people. Cognitive impairment can lead to dependence on the help of others. This study aims to analyze factors associated with cognitive impairment among older persons in Indonesia. Cognitive impairment is measured by difficulty with memory or concentration, derived from Susenas September 2018. The size of the samples is 26,010 people aged 60 years and over and analyzed using multinomial logistic regression. Cognitive impairment is divided into three categories: Normal Cognitive, Mild Cognitive Impairment or MCI, and Dementia. This study found that 17.08 percent of the elderly in the sample had MCI, and 0.86 percent had dementia. The result also showed that age, gender, marital status, social activity, and economic level are associated with MCI and dementia. However, the results showed that there are relationships between education level and living arrangements only found among elderly with MCI but not the incidence of dementia. Future studies are suggested to add other factors such as food consumption, physical activity, and cognitive activity to have more understanding of the causes of cognitive impairment in the elderly in Indonesia.